IMPLEMENTASI NILAI DASAR PERJUANGAN HIMPUNAN MAHASISWA ISLAM TERHADAP PEMBINAAN KADER HMI KOTA PALEMBANG - Heryati Heryati; Yusinta Tia Rusdiana (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
Abstract-The thoughts of Cak Nur still greatly affect the HMI cadres of Palembang Branch. Therefore, this paper aims to reveal the thoughts of Cak Nur that affect the HMI cadres Palembang Branch, especially the thoughts contained in NDP HMI he has compiled. This study is a field study focused on assessing the implementation of NDP HMI in cadre development on HMI Palembang Branch by using qualitative descriptive method with inductive paradigm. The methods and paradigms are chosen in consideration of the analysis of research problems that require some information from below under the principles of qualitative research. Historical, sociological, and phenomenological approaches are an option for the purpose of research can be achieved well. The type of data in this study is qualitative-quantitative. The research data consist of primary and secondary data. The results of this study are first, the NDP was originally the working paper of PB HMI period 1966-1969 compiled by Cak Nur. At that time, he served as Chairman. The historical setting of this NDP concept, because Cak Nur calling to HMI cadres have a pocket book. NDP HMI is a reflection of Islamic thinking, humanity and keindonesiaan typical HMI. Second, the NDP for HMI cadres Palembang branch is the identity of the cadre or identity itself, and the values that must be used as the basis in the struggle of life, whether in organizing, in community, and in the state. To arrive at the implementation stage of the NDP for its cadres, HMI Palembang branch provides the same portion for each cadre to obtain teaching and education on NDP in stages; starting from the Introduction of Prospective Members (MAPERCA), Kader I Training (LK I), LK II, LK III, to the highest level, the NDP Instructor Training. All this is done so that every cadre has the opportunity to study, understand, animate and actualize the values contained in the NDP. Thirdly, Cak Nur, as an organizational and intellectual figure for the HMI cadres of Palembang branch, has a significant influence, especially the thoughts contained in NDP HMI which are always studied and actualized in organizational life, society and state.Keywords: HMI, Cag Nur, LK